XML Certification Quizzer. - Amoussou, Joel (XML journal :the ultimate enterprise resource.)
In this month's "XML Certification Quizzer," we are going to review some interesting aspects of the syntax of XML and related technologies. You can learn more about the syntax of the language by running the sample code in the questions with an XML parser or an XSLT processor. The skills you'll learn here will prepare you for IBM Test 141 on XML and related technologies.